Online Predators, An Internet Insurgency: A Field Manual for Teaching and Parenting in the Digital Arena - Lee, Jeffrey A. (Rowman & Littlefield Publishers, 2023)
In Online Predators: An Internet Insurgency, Jeffrey A. Lee brings his ten plus years’ experience in the fight against online child exploitation to bear in an easy to follow guide for all with a stake in the life of a child. This book equips parents, guardians, extended family, educational professionals with practical strategies to help keep kids safe in a technology connected world. Instead of focusing on ever changing technology, Lee proposes a key fundamental change in the fight against online predation—develop an insatiable curiosity about their child’s online life, then get in the front lines and stay there.